PENGEMBANGAN MEDIA PEMBELAJARAN CAD SEBAGAI PENUNJANG PERKULIAHAN PENDIDIKAN TEKNIK BANGUNAN DAN PEMBELAJARAN SMK JURUSAN BANGUNAN - Setiawan, Abdul Haris (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2013)
The objectives of this study are; (1) designing instructional media Computer Aided Design (CAD) for Pendidikan Teknik Bangunan (PTB) PTK FKIP UNS and Vocational High School (SMK) Building Construction Department, (2) to produce a viable medium of learning CAD, (3) determine whether the CAD design of learning media can improve the competence of students in PTB and vocational students Building Construction Department.The designing of instructional Media is made at Vocational High School (SMKN 5 Surakarta) given in the form of video instructional media learning is needed. The method used in this research is the development of research methods. Criteria for success of this study refers to the successful implementation of product testing. The success include process and outcome indicators: (1) it is compliance with aspects of the substance of learning, aspects of media and instructional aspects, (2) It fits for use as a medium of learning, (3) vocational students receive as an innovative product in the learning, (4) it can help Vocational High School students (SMK) in learning more effective and efficient.The conclusion of this study include: (1) CAD design of instructional media for PTB and SMK is carried out in accordance with the procedures, (2) media products of CAD Learning Media is worth to use in PTB FKIP UNS and SMK Building Construction Department, (3) CAD instructional media products can increase the competence of student at PTB and vocational students Building Construction Department.